The Effect of Ozone and Zeolite Concentration to the Performance of the Treatment of Wastewater Containing Heavy Metal Using Flotation Process - Karamah, Eva Fathul; Bismo, Setijo; Simbolon, Hotdi M. (Makara Journal of Technology, 2008)
The Effect of Ozone and Zeolite Concentration to the Performance of the Treatment of Wastewater Containing Heavy Metal Using Flotation Process. Industrial wastewater which contains heavy metal cannot be disposed to the environment directly, due to its toxicity. In this research, separation of metal from wastewater was conducted by sorptive flotation method, using Lampung natural zeolite as bonding agent. The most common diffuser used in the flotation process is air or oxygen. In this research, ozone is used as diffuser because it is a stronger oxidant and more dissolvable in water than oxygen. Besides, ozone is a coagulant aid and disinfectant. With ozone as diffuser, it is expected that the process become faster with higher efficiency. This research was conducted to determine ozone effectiveness as diffuser, compared with other diffuser, and also to determine optimum concentration and effectiveness of zeolite in flotation of iron, nickel and copper. The research result shows that separation of iron with air diffuser is 90.8%, air-oxygen diffuser is 95.7%, air-ozone (from air) diffuser is 99.7%, and air-ozone (from oxygen) diffuser is 99.7%. Natural zeolite is effective as bonding agent with optimum concentration equal to 2 gram/liter, producing separation percentage for iron equal to 99.70%, copper equal to 88.98% and Nickel equal to 98.46%.